Analysis of Environmental Indicators Eco Management and Audit Scheme (EMAS) to Improve Energy Efficiency Using the Sustainable Overall Throughput Effectiveness (SOTE) Indicator in the Production Department (Case Study: XYZ Company, Pasuruan, East Java) - Cayo Pungki Andrianto; Sukendro Broto Sasongko (Journal of Mechanical Engineering, Science, and Innovation, 2026)
The rapid increase in global energy demand, driven by industrial growth and the challenges of climate change, makes energy efficiency a top priority in the manufacturing sector. Industrial cooling and production processes consume large amounts of electricity and water, contributing to high operational costs and environmental impacts. This research aims to evaluate and improve energy efficiency in a manufacturing production process through the integration of the Sustainable Overall Throughput Effectiveness (SOTE) and Eco-Management and Audit Scheme (EMAS) methods. The research was conducted using a case study approach at XYZ Company, a multinational manufacturer of heat exchangers operating in Indonesia. Electricity and water consumption data for 2024 were analyzed, focusing on a selected production process with high energy intensity. The EMAS framework was used to identify sources of energy and water inefficiency through environmental audits, while SOTE was applied to evaluate production performance by considering availability, performance, quality, and sustainability index parameters. The research results indicate that the integration of SOTE and EMAS can provide a comprehensive and structured approach to identifying energy waste without sacrificing the quality of production output. This study proves that improving energy efficiency can be systematically integrated into operational performance management, thereby supporting the achievement of sustainability targets while increasing productivity. This integrated approach provides a practical reference for manufacturing companies in aligning operational excellence with environmental sustainability.